A “gaveta da história”: cultura histórica e historiográfica na escrita de Raimundo Nonato da Silva (1980-1990) - Morais, Hélia Costa (2018)
Raimundo Nonato da Silva was a potiguar intellectual who, throughout his career, maintained relations with several institutions of power and knowledge; such as the Historical and Geographical Institute of Rio Grande do Norte (IHGRN) and the North Rio Grande de Letras Academy (ANRL). These institutions helped to project it intellectually through more than 80 published books. Professor, memoirist, historiographer, jurist, among other functions, has extensive bibliographical production in the fields of memory, history, chronic, etc. The present work intends to understand the narrative representations produced by his writing about the past, assessing his relations with the construction of a Historical Culture (GADAMER, 2009) for the West Potiguar region and the way Historiographic Culture (DIEHL, 2002, 2009) influenced this process. To do so, it will reflect on how the time and space categories appear in the construction of their narrative around the region. It is therefore accepted that Raimundo Nonato acted consciously or unconsciously, as an architect in a process that represented a historical consciousness in the production of a past for spatiality. This time we will use as a source the collection of books My Memories of the Potiguar West, written between the 1980s and 1990s; as well as, part of the active and passive correspondence given along the proposed temporal cut. It is admitted that to consider such historical and historiographic course unveils and historicizes practices of knowledge and power crystallized over time.